PENGARUH TRANSAKSI PIHAK-PIHAK HUBUNGAN ISTIMEWA TERHADAP KINERJA PERUSAHAAN - Savitri, Maulita Prima; Luhgiatno, Luhgiatno (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to examine sales, purchases, accounts receivable and payable have an effect on company performance. The population in this study are manufacturing companies listed on the IDX in 2014-2018. Sampling was carried out using purposive sampling method with the number of companies as many as 61 companies and a sample size of 60. The type of data used in this study is secondary data. The data collection method is done through a documentation approach. The data analysis technique used descriptive statistical analysis, classical assumption test, and multiple linear regression analysis with the help of SPSS. The results of this study indicate that sales to special parties have an effect on company performance, purchases to special parties have an effect on company performance, receivables to special parties have an effect on company performance and payable to special parties have an effect on company performance.Keywords: sales, purchases, accounts payable, receivables and company performance.